Statin-induced myopathy and the benefit of oral administration of coenzyme Q10 - Kurniawan, Dede Indra (Curtin University, 2007)
Background. Muscle cramps are one of the adverse affects suffered by hypercholesterolemia patients who are treated with statins. Besides reducing cholesterol levels, statins also reduce coenzyme Q10 (CoQ10) blood levels. One of several hypotheses of pathophysiology for statin-induced muscle cramps is reduced level of CoQ10. Besides being a very important antioxidant, CoQ10 also functions as a transmembrane proton conductor and an electron carrier between NADH and succinate dehydrogenases and the cytochrome system, which is needed for phosphorylation of ADP into ATP. Therefore, a decrease in the CoQ10 tissue levels, as reflected in its reduced blood levels, may contribute to the muscle function impairment. Researchers have proven that statins, drugs used to lower cholesterol, are able to reduce CoQ10 blood levels.Null Hypothesis. The administration of CoQ10 will have no effect on the frequency, severity and/or duration of muscle cramps amongst statin users.Aims. This study aimed to assess factors that might influence the development of statininduced myopathy manifested as muscle cramps, including the respondent’s age and sex; the dose and duration of their statin therapy; muscle symptoms (nature, duration and whether or not they have changed with statin use); other medicines consumed; and, other diseases suffered and to investigate the efficacy of oral CoQ10 supplements in reducing muscle cramps in statin users and non-users.Methods. The Study was comprised of two phases: Phase 1 the Muscle Adverse Effect Survey and Phase 2 the Coenzyme Q10 for Muscle Cramps Study. Data collection for Phase 1 took place from January 2006 to April 2006 in 45 community pharmacies throughout Western Australia. The second phase of the study, the clinical trial, took place through School of Pharmacy, Curtin University of Technology, from May 2006 to December 2006.Results. In the first phase of the study, the Muscle Adverse Effect Survey, it was found that the prevalence of myopathy amongst statin users was 22.3% (205/920). Amongst the respondents with muscle symptoms, 73/205 (35.6%) reported their muscle symptoms had worsened on using statins. Assuming non-respondents did not suffer from muscle problems reduced the overall incidence of potential statin-induced myopathy to 73/920 or 7.93%. It was found that atorvastatin was the most commonly prescribed statin (59.3%), followed by simvastatin (29.8%), then pravastatin (10.4%) and fluvastatin (0.6%). Despite the high use of atorvastatin, the incidence rate of myopathy by atorvastatin users was found to be similar with other statins. The most common muscle symptoms were night cramps (54.6%), muscle aching (52.7%), and fatigue (49.3%), while the most commonly affected area of the body was the calves (62%).Statistical analysis with multiple logistic regression showed increasing age, heart failure and the use of cortisone-like drugs increased the risk of muscle symptoms among statin users. It was found that, for every 1-year increase in age, the odds of suffering from muscle symptoms increased 1.039 (95% CI 1.019 – 1.061). Furthermore, taking cortisone-like medication increased the odds of suffering muscle symptoms 16.4 times (95% CI; 2.2 – 124.3), while participants with heart failure were 9.3 times (95% CI 1.2 – 73.2) more likely to develop muscle symptoms when prescribed statins.The second phase of the study, the Coenzyme Q10 for Muscle Cramps Study, was a single blind, placebo-controlled, cross over, 6-week evaluation of the benefits CoQ10 in reducing muscle cramps amongst statin users and non-users. It was found that on average, that statin users experienced a significant reduction in the severity of their muscle cramps, as indicated by lower average pain scores, during the period they were on CoQ10 (6.36 ± 0.75) compared with placebo (7.37 ± 0.85; p = 0.028). Furthermore, patients also experienced significantly shorter cramp duration when they were on CoQ10 (4.88 ± 0.84) than on placebo (5.84 ± 0.84; p = 0.001). In contrast, amongst non-statin users (who were used as controls), there were no significant differences between CoQ10 and placebo efficacy in all assessed variables.Conclusion. This study revealed that muscle symptoms were common among statin users, particularly those suffering from heart failure, taking corticosteroids, and increasing age. Furthermore, the administration of CoQ10 100 mg per day was safe and effective in reducing severity and duration of muscle cramps amongst statin users. However, these later findings need to be confirmed by larger, double blind, placebo controlled studies.